Direct evidence of particle-phase reactions of aldehydes and ketones with atmospheric secondary organic aerosol components - Siqi Tang; Yindong Guo; Xiaolei Yang; Zhen Song; Yali Jin; Shuhui Xue; Jianghe Xiong; Defeng Zhao (Atmospheric Environment, 2026)

Cobalamin-autonomous Trichlorobacter facilitates robust In situ bioremediation of halogenated solvents - Xuhao Wang; Hengyi Liao; Xin Wang; Yuanzhi Wang; Defeng Li; Honglin Ma; Jiaojiao Yang; Xinyue Qian; Hongyan Wang; Qingyu Li; Zongming Xiu; Yi Yang (Journal of Hazardous Materials, 2026)

Development and validation of CFDT code for fission product release analysis of spherical and cylindrical TRISO-based fuel element in HTGRs - Liying Zhang; Defeng Yang; Xiaoxia Wang; Aijun Mi; Guoming Liu; Liangzhi Cao; Jinkai Liu; Shiyu Liu; Pengpei Xie; Qingmin Zhang (Annals of Nuclear Energy, 2026)

Phthalate esters in cooking organic aerosols from various edible oils - Xiaolei Yang; Shuhui Xue; Qingpeng Meng; Siqi Tang; Chunlin Li; Lina Wang; Defeng Zhao (Journal of Environmental Sciences, 2026)

Numerical Simulation of Large Deformation Movement Process of Underwater Slope Subjected to Seismic Loads: A Case Study from the St. Niklausen Landslide - Mingzhe Wei; Zhongde Gu; Ze Rong; Yang Liu; Yang Lu; Defeng Zheng; Tingkai Nian (Journal of Marine Science and Engineering, 2026)
Large deformation runout is a key factor in assessing the hazards posed by underwater landslides. However, conventional kinematic analyses often neglect both the progressive degradation of slope materials and the hydrodynamic response accompanying the interaction between the moving mass and the overlying water. Taking the well-documented St. Niklausen underwater landslide as a representative case, this study employs a coupled Eulerian–Lagrangian (CEL) model to investigate the earthquake-triggered initiation, large deformation movement, and hydrodynamic response of the landslide. A Python 2.7.15-based stress mapping method is developed to establish an accurate initial geostatic stress field for the irregular slope profile. The numerical model reproduces the principal stages of landslide initiation, runout, and deposition. The results reveal a progressive retrogressive failure mechanism in which successive sliding masses interact through a high-strength compression zone. The rear sliding mass continuously transfers compressive work to the frontal mass, thereby maintaining its downslope movement and indirectly promoting basal erosion to a maximum depth of approximately 6.2 m. In addition, rapid landslide motion generates pronounced vortical flow in the overlying water. These flow structures reflect the hydrodynamic response induced by landslide motion, although their net influence on basal resistance and final runout cannot be isolated from the present coupled simulation. These findings clarify the internal mechanical evolution of underwater landslide movement and characterize the accompanying hydrodynamic response, providing a methodological basis for assessing landslide mobility and related underwater hazards.

Methodological investigation of emergency rescue vertical timber supports in building-ruin scenarios: experiments, simulations, and applications - Defeng Xu; Feifei Sun; Chong Xu; Junwu Dai; Yongqiang Yang (Bulletin of Earthquake Engineering, 2026)

Microplastic accumulation in paired human breast tumor and para-tumor tissues and exploratory clinical associations - Limin Jia; Yanni Song; Yufeng Guo; Fuyu Yang; Qiyan Guan; Weihan Zhang; Yang Liu; Defeng Xing; Yanhong Lv (Journal of Hazardous Materials, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Performance evaluation of building-integrated photovoltaic windows with triple-glazing: Summer assessment in cold climate - Chunwen Xu; Xintao Tian; Rumei Yang; Shasha Song; Fei Han; Defeng Kong; Yelin Zhang (Energy and Buildings, 2026)

Bioaugmentation of strain Bacillus sp. hex-HIT36 towards industrial wastewater 1-Hexadecene removal in biological aerated filter reactors - Lei Yang; Yijie Liu; Yuxin Pan; Xue-Ting Wang; Wei Wang; Xijun Xu; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2026)

Sesquiterpenoids from Euphorbia esula L. - Defeng Yan; Miaomiao Zhang; Dan Tang; Yuqing Song; Liu Liu; Haiqing Zhao; Nurmirza Begmatov; Orzimat Turdimatovich Turginov; Bo Zhao; Hequn Yang; Guoan Zou (Phytochemistry, 2026)

Experimental investigation on the high-speed suspension hexamaran in head waves - Xin Liu; Jinglei Yang; Defeng Wu; Haibin Wang; Jingheng Wu; Liang Hou; Lei Du; Qian Wan (Ocean Engineering, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Chitin nanocrystal-stabilized Pickering emulsion for multimodal sensing - Yuchen Chao; Sumin Yu; Xuexue Ding; Mengmeng Yang; Defeng Wu (Carbohydrate Polymers, 2025)

Carbon pathways in soil: unraveled by 13C natural abundance - Ying Wang; Anna Gunina; Defeng Yang; Tao Sun; Yakov Kuzyakov (Soil Biology and Biochemistry, 2025)

Self-regulating adaptability of biofilm microbiomes enhances manganese and ammonia removal in microbial electrochemical filters under dioxane exposure - Sitong Liu; Kun Feng; Dawei Zhang; Yang Liu; Jing Wang; Baiyun Lu; Defeng Xing (Journal of Hazardous Materials, 2025)

Simultaneous denitrification and phosphorus removal in MBfR with methane as the sole carbon source - Xiaowei Lv; Huihui Zhou; Jie Yang; Jiayin Hao; Zheng Zhong; Kun Feng; Defeng Xing (Journal of Environmental Management, 2025)

Nutrient cycles in transition: C:N:P stoichiometry by forest conversion to plantations - Ying Wang; Anna Gunina; Peter B. Reich; Defeng Yang; Han Y.H. Chen; Yakov Kuzyakov; Yongxing Cui; Jingwen Chen; Zhiming Guo; Tao Sun (Forest Ecology and Management, 2025)

Reassessing systemic blind spots in modern water disinfection paradigms - Yang Liu; Jialiang Gu; Kun Feng; Yangyang Zhang; Zheng Zhong; Sitong Liu; Defeng Xing (Journal of Hazardous Materials, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Precise baseline determination for the four-satellite InSAR constellation HT-01 with ambiguity resolution constraints - Dachen Peng; Shibo Guo; Defeng Gu; Kai Shao; Houzhe Zhang; Ruiyun Yang; Jufeng Lu; Jiangkai Liu; Haoseng Wang; LiuPeng Huang (Advances in Space Research, 2025)

Altered functional connectivity within and between resting-state networks in ulcerative colitis - Yanjun Ren; Kaizhong Xue; Huijuan Xu; Lijie Hao; Quchuan Zhao; Tianyu Chi; Hongwei Yang; Xiaojing Zhao; Defeng Tian; Huihong Zhai; Jie Lu (Brain Imaging and Behavior, 2025)

Effectiveness of microbial-induced carbonate precipitation for mitigating the hydraulic erosion of the riverbank - Defeng Yang; Ying Wang; Guobin Xu; Donghao Huang; Nan Shao; Lili Zhou (Journal of Environmental Management, 2025)

CoOX composite Pr0.4Sr0.6Co0.2Fe0.8O3-δ perovskite was used to obtain an IT-SOFC cathode with high electrocatalytic activity - Yuqian Wang; Defeng Zhou; Weiyi Zhang; Jie Yang; Qingyuan Sheng; Xiaofei Zhu; Jinghe Bai (Fuel, 2025)

Applying machine learning and genetic algorithms accelerated for optimizing ethanol production - Xu Yang; Nianhua Chen; Hui Yu; Xinyue Liu; Yujie Feng; Defeng Xing; Yushi Tian (Science of The Total Environment, 2024)

Experimental study of a high-speed suspension hexamaran in calm water - Xin Liu; Jinglei Yang; Defeng Wu; Liang Hou; Lei Du; Qian Wan (Ocean Engineering, 2024)

Genome and metabolome analysis of Bacillus sp. Hex-HIT36: A newly screened functional microorganism for the degradation of 1-hexadecene in industrial wastewater - Lei Yang; Chuan Chen; Xijun Xu; Xue-Ting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee (Environmental Research, 2024)

Linking metabolomics to machine learning reveals the metabolic fates of the refractory industrial pollutant 1-Hexadecene - Lei Yang; Xijun Xu; Jin Yan; Wei Wang; Xueting Wang; Defeng Xing; Nanqi Ren; Duu-Jong Lee; Chuan Chen (Chemical Engineering Journal, 2024)

Flexural behavior and design methodology for bamboo scrimber-aluminum plate composite beams - Ye Sheng; Defeng Tu; Feiyu Liao; Yuxing Yang; Chenggen He; Wei Zhang; Cheng Meng (Engineering Structures, 2023)

Observer-based adaptive integral terminal sliding mode formation control for a vessel train with obstacle avoidance - Peng Luo; Defeng Wu; Kexin Yuan; Yang Yang (Ocean Engineering, 2023)

Capsular polysaccharide mediates Streptococcus agalactiae to resist Nile tilapia macrophage phagocytosis - Yanjian Yang; Meng Chen; Zhelin Wu; Defeng Zhang; Huiyan Lin; Xiayi Wei; Biao Han; Zheng Guo; Jianmin Ye (Aquaculture, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

Streptococcus shenyangsis sp. nov., a New Species Isolated from the Oropharynx of a Healthy Child from Shenyang China - Defeng Liu; Chunling Xiao; Xinming Li; Ye Sun; He Qi; Yang Zou (Current Microbiology, 2021)

Description and genomic characterization of Streptococcus symci sp. nov., isolated from a child’s oropharynx - He Qi; Defeng Liu; Yang Zou; Nan Wang; Han Tian; Chunling Xiao (Antonie van Leeuwenhoek, 2021)
Using the culturomics approach, we isolated a new Streptococcus species, strain C17 T , from the oropharynx mucosa sample of a healthy 5-year-old child living in Shenyang, China. We studied the phenotypic, phylogenetic, and genomic characteristics of strain C17 T , which was identified as a Gram-positive, coccus-shaped, non-motile, aerobic, catalase-negative bacteria. Its growth temperatures ranged from 20 to 42 °C, with optimal growth at 37 °C. Acid production could be inhibited by two sugars, trehalose and raffinose. In C17 T , the reactions for enzyme lipase (C14) were confirmed to be negative, whereas those for alkaline phosphatase, α-glucosidase, and hippuric acid hydrolysis were positive. The C17 T genome contained 2,189,419 base pairs (bp), with an average G+C content of 39.95%, encoding 2092 genes in total. The 16S ribosomal RNA sequence showed 99.8% similarity with the newly identified Streptococcus pseudopneumoniae ATCC BAA-960 T . The main fatty acid components in C17 T were C16:0, C18:1 w7c, C18:0, and C18:1 w9c, all of which can be found in other species of the Streptococcus genus. Strain C17 T showed high susceptibility to clindamycin, linezolid, vancomycin, chloramphenicol, and cefepime, and moderate susceptibility to erythromycin. The obtained dDDH value between strain C17 T and the closest species was 52.9%. In addition, the whole genome sequence of strain C17 T had an 82.21–93.40% average nucleotide identity (ANI) with those strains of closely related Streptococcus species, indicating that the strain C17 T was unique among all Streptococcus species. Based on these characteristics, we determine that C17 T is a novel species, named Streptococcus symci sp. nov. (= GDMCC 1.1633 = JCM 33582).

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

Regulation of Thermostable Direct Hemolysin and Biofilm Formation of Vibrio parahaemolyticus by Quorum-Sensing Genes luxM and luxS - Muhan Guo; Zhijia Fang; Lijun Sun; Dongfang Sun; Yaling Wang; Can Li; Rundong Wang; Yang Liu; Hanqiao Hu; Ying Liu; Defeng Xu; Ravi Gooneratne (Current Microbiology, 2018)

Reduced antigen presentation capability and modified inflammatory/immunosuppressive cytokine expression of induced monocyte-derived dendritic cells from peripheral blood of piglets infected with porcine circovirus type 2 - Ning Yang; Jiandong Li; Qian Yang; Jinzeng Qiao; Defeng Cui; Fenghua Liu; Huanrong Li; Shuanghai Zhou (Archives of Virology, 2018)